Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning di Kelas III Sekolah Dasar - Ilhamdi, Robi; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research aims to describe improving learning outcomes in integrated thematic learning using the problem based learning model in class III elementary school. The research is included in classroom action research which uses quantitative and qualitative approaches. In its implementation, this research was carried out in 2 cycles. Each cycle has stages of planning, implementation, observation and reflection. The subjects of the research were all 16 class III students at SDN 07 Garabak Data. In cycle I, the RPP was observed with an average of 72% (C) and increased in cycle II with a value of 97% (A). The results of observing teacher activities in cycle I with an average of 62% (C) experienced an increase in cycle II, namely 96% (A). Furthermore, student activity in cycle I with an average gain of 78% (B) and an increase of 92% (A) in cycle II. Meanwhile, student learning outcomes in cycle I obtained an average score of 77.74%, increasing in cycle II with an average score of 89.92%. It can be concluded that the problem-based learning model can improve student learning outcomes in integrated thematic learning in class III elementary school.